Phylogeny, taxonomy and nomenclature:the problem of taxonomic categories and of nomenclatural ranks - Dubois, Alain (Zootaxa, 2007)
The use of ranks and nominal-series in zoological nomenclature has recently been challenged by some authors who support unranked systems of nomenclature. It is here shown that this criticism is based on a double misunderstanding: (1) the confusion between nomenclatural ranks and taxonomic categories; (2) the request for a monosemic nomenclatural system, not for scientific reasons, but to please non-taxonomists, especially customers of the web. It is here argued that nomenclatural ranks and taxonomic categories should be clearly distinguished and designated by different terms, and that the Code should be modified in order to make this distinction clear. Whereas taxonomic categories have biological definitions, nomenclatural ranks do not, as they express only a position in a taxonomic hierarchy. If used consistently (which is not always the case), the system of nomenclatural ranks is very useful for the storage and retrieval of taxonomic and phylogenetic information. Taxa referred to a given rank in different groups cannot therefore be considered equivalent by any criterion, so that using ranks for comparisons between taxa (e.g., for biodiversity richness assessment) is irrelevant and misleading. Although the current Code needs to be improved in several respects, the superiority of this nomenclatural system, which is theory-free regarding taxonomy as it relies on ostensional allocation of nomina to taxa rather than on intensional definitions of nomina, is again stressed. It is suggested that all taxonomists should follow the Code for the allocation and validity of nomina, whatever taxonomic theory they favour, and in particular whatever kinds of definitions or diagnoses they wish to use for taxa. This would avoid the considerable loss of manpower, time and energy that would be required by the implementation of a new nomenclatural system (e.g., in order to require “phylogenetic definitions” for nomina, or to make nomenclature fully monosemic), and the confusion that would result for most users of nomina. The new paradigm imposed to biology by the combination of the taxonomic impediment and of the biodiversity crisis requires from taxonomists, who are already considerably much less numerous than required by this new situation, to concentrate on what should be their priority at the beginning of the century of extinctions, namely the inventory of the living species of our planet before they get extinct.